Business cycles and the impact of labour market programmes - Oddbjørn Raaum; Hege Torp; Tao Zhang (University of Oslo, Department of Economics, 2002)
By comparing mean outcomes for a large number of matched samples of participants and nonparticipants we estimate individual earnings effect of the Norwegian labour market training programme (LMT) targeted at unemployed adults in the years 1991-1996. The average training effect on the trained is positive, even after three years. The training effect is positively correlated with post-training job opportunities in the (local) labour market, when job opportunities are measured by time-varying human capital adjusted national and regionspecific exit rates from unemployment.
Keywords: C14; J64; J68; 330; Causal effects; matching estimators; training unemployed; impact on annual earnings; Arbeitsmarktpolitik; Lohn; Norwegen; Berufliche Integration